Neuroticism as a Moderator of the Relationship Between Peer Conformity and Cyberbullying - Putri, Agustin Andhika; Febriani, Arum (Gadjah Mada Journal of Psychology (GamaJoP), 2025)
Cyberbullying is a phenomenon that often occurs in adolescents and can be caused by conformity or personality. This study aimed to evaluate whether neurotic personality can strengthen or weaken the relationship between conformity and cyberbullying in adolescents. The participants were 140 adolescents aged 12–15 years old, all of whom were active social media users and had been involved in cyberbullying. Cyberbullying was measured on a scale created by the researchers (α = 0.863), conformity was measured using a peer conformity scale (α = 0.846), and neuroticism was measured using a scale that had been previously adapted into the Indonesian language and culture (α = 0.766). Data were analyzed quantitatively using PROCESS. The results showed that low levels of neuroticism could moderate or strengthen the relationship between conformity and cyberbullying. Future researchers might test moderating variables other than neuroticism to obtain new findings. Based on the current study, parents are advised to help children select their friendship environments to prevent cyberbullying behavior. Schools can create intervention programs to prevent cyberbullying, especially for adolescents who display neuroticism. School counselors and parents can create a positive friendship environment so that adolescents do not become perpetrators or victims of cyberbullying. Parents are additionally advised to limit the use of digital devices among their adolescents.